Reviewing an Efficiency of the Use of Fuel and Power Resources for the Industry of Ukraine - Kavertsev, Valeriy Leonidovich; Dyahiliev, Vadym Oleksandrovych (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2017)
The purpose of this scientific paper was to analyze actual problems related to the use of fuel and power resources and faced today by the power economy sector in Ukraine. An efficient use of these resources provides a stable power supply for the State. At the present time Ukraine survives a considerable rise in price for natural gas and other traditional power resources. This scientific paper describes the basic measures taken to decrease the cost price of used power resources and reduce the amount of expensive fuel used by industrial companies in Ukraine. This paper gives the statistics of the use of fuel and power resources by the companies of mining and smelting sector that are the key consumers of power resources. It should be noted in conclusion that Ukraine has a considerable potential for the reduction of the consumption of fuel and power resources due to the optimized use of secondary power resources through the manufacture of new boilers and the modernization of old boiler units that would enable the combustion of the fuels of a wide range. The wanted effect can be achieved through the improvement of firing burners installed in the boilers.